2020
DOI: 10.1016/j.cmi.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of invasive non-typhoid Salmonella infection: a nationwide population-based registry study

Abstract: Objectives: Non-typhoid Salmonella (NTS) may invade beyond the intestine, causing bacteraemia, sepsis, and infection of normally sterile sites. The epidemiology of invasive NTS (iNTS) infection is underresearched. We determined trends, risk factors, serotype distribution, antimicrobial resistance (AMR), and attributable sources of iNTS infection in a high-income setting. Methods: 22,837 records of culture-confirmed human salmonellosis cases and 10,008 serotyped Salmonella isolates from five putative animal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 21 publications
14
31
3
Order By: Relevance
“…On the basis of the current findings, we recommend against routinely using antimicrobials to treat uncomplicated NTS gastroenteritis in cases of high CRP level. This finding is consistent with that of Mughini-Gras et al (2020) who reported that iNTS isolates were generally less resistant than non-iNTS isolates (Mughini-Gras et al, 2020;Ke et al, 2020). NTS bacteremia in this study tended to develop in young children with prolonged fever.…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the current findings, we recommend against routinely using antimicrobials to treat uncomplicated NTS gastroenteritis in cases of high CRP level. This finding is consistent with that of Mughini-Gras et al (2020) who reported that iNTS isolates were generally less resistant than non-iNTS isolates (Mughini-Gras et al, 2020;Ke et al, 2020). NTS bacteremia in this study tended to develop in young children with prolonged fever.…”
Section: Discussionsupporting
confidence: 93%
“…We found that Salmonella Typhimurium was the most common serotype of NTS infection cases among children in Ningbo (62.7%), which was in accordance with the findings of studies performed in Guangzhou, southern China [4,33,34]. However, some studies from other regions of China [5,35], the United States [11], the Netherlands [14], and Greece [36] reported that Salmonella Enteritidis was the most common serotype, followed by Salmonella Typhimurium. The modes of NTS transmission may be a key factor in the geographical variation in serotype distribution.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 89%
“…A few studies have explored the health consequences of antimicrobial-resistant NTS, with conflicting results reported. The results that patients with antimicrobial-resistant NTS infection more likely to have invasive disease and severe outcomes were reported in the United States [11], while a study in the Netherlands found that iNTS isolates were generally less (multi-) resistant than non-iNTS isolates were [14]. Our results were similar to the latter.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 85%
See 1 more Smart Citation
“…Its mortality has been significantly reduced by implementation of appropriate antibiotic treatment but the increase in beta-lactam and fluoroquinolone resistance of Salmonella strains is a growing public health problem [3][4][5][6]. Depending on the immune status of the patient, NTS can also cause extraintestinal and bloodstream infections with various manifestations such as meningitis, septic arthritis, abscesses and osteomyelitis [7,8]. Some serovars which are highly adapted to animal hosts can cause complicated disease in humans.…”
Section: Introductionmentioning
confidence: 99%